The global burden of Klebsiella pneumoniae-associated lower respiratory infection in 204 countries and territories, 1990–2021: Findings from the global burden of disease study 2021 - Juanjuan Li; Liang Xu; A. Fang Zuo; Ping Xu; Kaizhi Xu (PLoS ONE, 2025)
This study investigates the global epidemiological burden of lower respiratory infections (LRI) attributable to Klebsiella pneumoniae from 1990–2021, using data from the Global Burden of Disease Study (GBD) 2021. The findings reveal that globally, disability-adjusted life years (DALYs) from Klebsiella pneumoniae-associated LRI decreased from 16,701,044 (95% UI: 14,220,055–19,183,469) in 1990–6,935,440 (95% UI: 5,953,328–8,007,786) in 2021, while deaths declined from 239,367 (95% UI: 212,553–268,072) –175,783 (95% UI: 158,749–193,924). The age-standardized DALYs rate dropped from 313.1 (95% UI: 266.6–359.7)–87.9 (95% UI: 75.4–101.5), and the death rate decreased from 4.5 (95% UI: 4.0–5.0)–2.2 (95% UI: 2.0–2.5). In 2021, the highest rates were observed in Oceania and Sub-Saharan Africa, particularly in Central African Republic, Niger, and Zimbabwe, while the lowest rates were found in Australasia, High-income North America, Eastern Europe, and East Asia, especially in the UAE, Australia, and Qatar. Higher rates were noted among both males and females under 10 and over 65 years old. Although most regions experienced decreases in age-standardized rates(ASR) from 1990–2021, Southern Latin America exhibited an increase. Additionally, age-standardized DALYs and death rates generally declined with increasing socio-demographic index (SDI). The global burden of LRI due to Klebsiella pneumoniae significantly decreased over the study period, but lower SDI regions, children, and the elderly remain vulnerable and require targeted interventions to further reduce this burden.